Perencanaan Pembangkit Listrik Tenaga Surya Kapasitas 54 kWP Off Grid Pulau Rani Desa Yamnaisu - Yusuf, Erwin; Jakariya (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This study presents the design of a 54 kWp off-grid Solar Power Plant (SPP) in Rani Island, Yamnaisu Village, Supiori Regency, Papua—an isolated region with limited access to the PLN electricity grid. The planning approach involved engineering design methods, including field surveys of electricity demand, solar irradiation potential, and technical specifications of solar panels and supporting components. Based on a daily energy demand of 199,394 Wh and a local solar potential of 3.707 kWh/kWp/day, the system was designed using 270 PV modules, 216 VRLA battery units, 18 Solar Charge Controllers (SCC), and 3 inverters. A performance simulation using PVsyst software showed an estimated annual energy production of 134 MWh, equivalent to a reduction of 63.9 tons of CO₂ emissions. The site plan and single line diagram demonstrate an efficient and secure configuration for areas with geographic challenges. The results confirm that the implementation of an off-grid SPP is an effective solution for rural electrification while contributing to the achievement of national renewable energy targets.